Factors Influencing Resistivity Inversion for CO2 Geological Storage Zones: A Quantitative Study - Chenguang Wang; Tianyang Li; Tao Yu; Xiao Feng; Hanghang Liu; Bingrui Du; Yichun Yang; Linjun Yang; Yaxuan Luo (Sensors)
This study establishes a homogeneous half-space and a horizontally layered two-layer background stratigraphy model using cross-borehole electrical resistivity tomography (ERT) based on an incomplete Gauss–Newton (IGN) method to investigate the resistivity inversion characteristics of CO2 storage zones. The effects of storage zone volume (<semantics data-eusoft-scrollable-element="1">VCO2</semantics>), storage zone resistivity (<semantics data-eusoft-scrollable-element="1">ρCO2</semantics>), background formation resistivity (<semantics data-eusoft-scrollable-element="1">ρf</semantics>), and CO2 diffusion on inversion results were systematically analyzed, and the mechanisms underlying the influence of different parameters on inversion imaging were explored. The results indicate that an increase in the <semantics data-eusoft-scrollable-element="1">VCO2</semantics> significantly affects the inverted resistivity. The <semantics data-eusoft-scrollable-element="1">ρCO2</semantics> can be well inverted within a certain range, but inversion accuracy decreases once the resistivity exceeds a threshold. The <semantics data-eusoft-scrollable-element="1">ρf</semantics> is a critical factor influencing inversion results; as the <semantics data-eusoft-scrollable-element="1">ρf</semantics> increases, the inverted resistivity values rise markedly, although this effect exhibits an upper limit. The study also uncovers the exponential nature of CO2 diffusion in the storage zone, where diffusion leads to exponential changes in resistivity and the delineation of the diffusion zone is enhanced by comparing pre- and post-injection resistivity differences. These findings offer valuable insights for CO2 storage monitoring, contributing to both safety assessments and the evaluation of storage stability in geological sequestration.